On the Asymmetric Longitudinal Oscillations of a Pikelner’s Model Prominence - Kraśkiewicz J.; Murawski K.; Solov’ev A.; Srivastava A.K. (My University, 2025)
We present analytical and numerical models of a normal-polarity quiescent prominence that are based on the model of Pikelner (Solar Phys.17, 44, 1971). We derive the general analytical expressions for the two-dimensional (2D) equilibrium plasma quantities such as the mass density and gas pressure, and we specify magnetic-field components for the prominence, which corresponds to a dense and cold plasma residing in the dip of curved magnetic-field lines. Adapting of these expressions, we numerically solve the 2D, nonlinear, ideal MHD equations for the Pikelner model of a prominence that is initially perturbed by reducing the gas pressure at the dip of magnetic-field lines. Our findings reveal that as a result of pressure perturbations, the prominence plasma starts evolving in time. This leads to antisymmetric magnetoacoustic–gravity oscillations and to the mass-density growth at the magnetic dip, and the magnetic-field lines subside there. This growth depends on the depth of the magnetic dip. For a shallower dip, less plasma is condensed, and vice versa. We conjecture that the observed long-period magnetoacoustic–gravity oscillations in various prominence systems are in general the consequence of the internal-pressure perturbations of the plasma residing in equilibrium at the prominence dip. © 2016, The Author(s).